Effects of Socioeconomic Status and Sociodemographic Features on Cardiovascular Disease. Mortality and Morbidity in Finland - Lammintausta, Aino (Annales Universitatis Turkuensis D 1068, 2013)
Despite declining trends in morbidity and mortality, cardiovascular diseases have a considerable impact on Finnish public health. A goal in Finnish health policy is to reduce inequalities in health and mortality among population groups. The aim of this study was to assess inequalities in cardiovascular diseases according to socioeconomic status (SES), language groups and other sociodemographic characteristics. The main data source was generated from events in 35-99 year-old men and women registered in the population-based FINMONICA and FINAMI myocardial infarction registers during the years ranging from 1988-2002. Information on population group characteristics was obtained from Statistics Finland. Additional data were derived from the FINMONICA and FINSTROKE stroke registers and the FINRISK Study. SES, measured by income level, was a major determinant of acute coronary syndrome (ACS) mortality. Among middle-aged men, the 28-day mortality rate of the lowest group of six income groups was 5.2 times and incidence 2.7 times as high when compared to the highest income group. Among women, the differences were even larger. Among the unmarried, the incidence of ACS was approximately 1.6 times as high and their prognosis was significantly worse than among married persons - both in men and women and independent of age. Higher age-standardized attack rates of ACS and stroke were found among Finnish-speaking compared to Swedish-speaking men in Turku and these differences could not be completely explained by SES. In these language groups, modest differences were found in traditional risk factor levels possibly explaining part of the found morbidity and mortality inequality. In conclusion, there are considerable differences in the morbidity and mortality of ACS and stroke between socioeconomic and sociodemographic groups, in Finland. Focusing measures to reduce the excess morbidity and mortality, in groups at high risk, could decrease the economic burden of cardiovascular diseases and thus be an important public health goal in Finland.

Sosioekonomisen aseman ja sosiodemografisten tekijöiden vaikutus sydän- ja verisuonisairauksien kuolleisuuteen ja esiintyvyyteen Suomessa Huolimatta laskevista sairastuvuus- ja kuolleisuustrendeistä, sydän- ja verisuonisairaudet ovat yhä merkittävä rasite Suomen kansanterveydelle. Yksi Suomen terveyspoliittinen tavoite on ollut pienentää väestöryhmien välisiä eroja terveydessä ja kuolleisuudessa. Tämän tutkimuksen tavoitteena oli tutkia väestöryhmittäisiä eroja sydän- ja verisuonisairauksien – erityisesti akuuttien sepelvaltimotapahtumien – sairastuvuudessa ja kuolleisuudessa Suomessa. Erityisesti pyrittiin selvittämään sosioekonomisen aseman, kieliryhmän ja muiden sosiodemografisten tekijöiden vaikutusta sydänsairastuvuuteen ja -kuolleisuuteen. Pääasiallinen aineisto oli FINMONICA ja FINAMI -sydäninfarktirekistereihin vuosina 1988-2002 rekisteröidyt sepelvaltimotapahtumat 35-99 –vuotiailla naisilla ja miehillä. Tieto sosioekonomisista ja sosiodemografisista ominaisuuksista saatiin Tilastokeskuksesta. Lisäksi tutkimuksessa käytettiin FINMONICA- ja FINSTROKE- aivohalvausrekistereiden sekä FINRISKI-tutkimuksen tietoja. Tuloluokka oli merkittävä akuuttien sepelvaltimotapahtumien kuolleisuuteen vaikuttava tekijä. Keski-ikäisillä alimman tulokuudenneksen miehillä kuolleisuus sepelvaltimotapahtumiin oli 5.2- kertaa ja ilmaantuvuus vastaavasti 2.7-kertaa suurempaa kuin ylimmän tulokuudenneksen miehillä. Naisilla erot olivat vielä suurempia. Naimattomilla sepelvaltimotapahtumien ilmaantuvuus oli noin 1.6-kertaa suurempaa ja ennuste huonompi sekä miehillä että naisilla iästä riippumatta. Suomenkielisillä miehillä oli suurempi ikävakioitu sepelvaltimotapahtumien ja aivohalvauksen esiintyvyys kuin ruotsinkielisillä miehillä Turussa. Erot eivät täysin selittyneet eroilla sosioekonomisessa asemassa. Perinteisten sydän- ja verisuonitautien riskitekijöiden tasoissa oli pieniä eroja kieliryhmien välillä, mikä voi osittain selittää eroja esiintyvyydessä ja kuolleisuudessa. Tutkimus osoitti, että Suomessa on edelleen merkittäviä väestöryhmittäisiä eroja akuuttien sepelvaltimotapahtumien ja aivohalvauksen esiintymisessä ja kuolleisuudessa. Väestöryhmien väliset erot sydänterveydessä ovat edelleen terveyspoliittinen haaste Suomessa.